Relationship between human capital investment and economic wellbeing: a case study in Business Apprenticeship Training Centers (BATCs), Kaduna, Nigeria - Haliru, Idris Yakubu; Abu Samah, Asnarulkhadi; Ahmad, Nobaya (Universiti Putra Malaysia Press, 2019)
The paper examined the effect of the human capital investment on economic wellbeing in business apprenticeship training centers (BATCs) in Kaduna, Nigeria. A structured questionnaire was used to obtain data from 267 respondents via cluster sampling from nine local government areas of the 23 local government areas in the state. The result indicates that there was a significant positive relationship between human capital investment and economic wellbeing. Hence, BATCs acts as a tool in capacity building endeavor among the youths in the state, and this is a part of state-sponsored community development process developing youth community.